OPTIMISATION OF AN EFFECTIVE ISLAMIC EDUCATION PROGRAM: A METHODOLOGICAL PERSPECTIVE - Patma Aulia; Miftahul Jannah; Tengku Indah Syafira; Afrahul Fadhilah Daulay (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2024)
The purpose of this study is to find out the importance of Islamic education methods in achieving the learning goals of Islamic religious education. This research uses a qualitative approach with a case study type. This research was carried out on Jl. Cucak Rawa I Perumnas Mandala, Medan Denai District, on Wednesday, May 22, 2024. In this study, the source of data obtained from this study is direct data, namely the researcher conducted direct interviews with educators or teachers related to Islamic Religious Education subjects at SD Negeri 066052 is Ahmad Ramadhana S.Pd.I. The data collection techniques used by the researchers in this mini research are observation, interviews and documentation. The results of the study show that the urgency of Islamic education methods is very important in achieving efficient, maximum, and comfortable learning goals. With the Islamic Education method, educators in Islamic Religious Education learning are able to produce intellectuals who believe and fear Allah SWT, intellectuals who are moral and moral and responsible. 2) In fact, the Islamic education methods applied have not been able to optimally achieve the goals of Islamic religious learning, this is due to the lack of learning media in schools. So that it becomes an obstacle for students in achieving the initial goals that have been set in learning Islamic Religious Education.